DNA restriction endonuclease analysis for localization of human beta- and delta-globin genes on chromosome 11. - Scott, A F (1979)
DNA from a clone of a mouse-human hybrid that retained a human chromosome consisting of the major part of chromosome 11 and region q25-26-qter of the X chromosome was digested with various restriction endonucleases, subjected to electrophoresis in agarose gels, and transferred to nitrocellulose filters. The restriction digest pattern of the clone, when hybridized with a 32P-labeled plasmid fragment containing human beta-globin gene sequences, was a composite of the normal human and mouse (A9) patterns. When back-selected in 6-thioguanine to eliminate the 11 translocation chromosome, the hybrid cells showed only the A9 restriction pattern. These results substantiate the localization of beta- and delta-globin genes to human chromosome 11 and exclude the region 11q23-qter as the site.